Microbial biofilms and the human skin microbiome - Brandwein, Michael (NPJ Biofilms Microbiomes, 2016)
The human skin microbiome plays an important role in both health and disease. Microbial biofilms are a well-characterized mode of surface-associated growth, which present community-like behaviors. Additionally, biofilms are a critical element in certain skin diseases. We review how the perception of the resident skin microbiota has evolved from the early linkages of certain microbes to disease states, to a more comprehensive and intricate understanding brought on by biofilm and microbiome revelations. Rapidly expanding arsenals of experimental methods are opening new horizons in the study of human–microbe and microbe–microbe interactions. Microbial community profiling has largely remained a separate discipline from that of biofilm research, yet the introduction of metatranscriptomics, metabolomics, and the ability to distinguish between dormant and active members of a community have all paved the road toward a convergent cognizance of the encounter between these two microbial disciplines.